Forcasting the Challenges of the Spatial Expansion of Tehran Metropolitan Area - Kazem Khazaei; Ismail Aliakbari; Hadi Veicy (جغرافیا و آمایش شهری منطقه‌ای, 2023)
Urban spatial expansion is the result of urbanization's control over the geographical space and it represents the process of land conversion to urban uses. The new trends of spatial expansion, especially in developing countries, are pregnant with numerous social, economic and environmental challenges, and forcasting the spatial expansion challenges is one of the useful methods for finding a sustainable spatial development strategy.The current research is a type of applied-developmental research that was carried out using a qualitative-quantitative method. In the qualitative part of Delphi group decision-making method, the opinion of experts regarding the identification, summarization and comparison of two indicators has been done, and in the quantitative part, the data has been analyzed using Interpretive Structural Modeling (ISM) in Micmac software.The findings of the research show that for internal migrations, population imbalance in the territory, instability of the settlement system, weak legal control, distribution of injustice, foreign migrations, social instability, poverty, destruction of the rural way of life, marginalization, increase in crime rate and Delinquency, poor social control, critical burden of the population, abnormal housing and the decline in the quality of life have the greatest influence and will play a role as the first level of challenging factors in the future of the metropolitan area of Tehran.The results of examining the challenges of the metropolitan area of Tehran show that among the components examined in the metropolitan area of Tehran, the highest level of influence and  is related to the migration component with an influence of 107.5, and this component is the most challenging factor in the future of the metropolitan area of Tehran. will work, and the lowest power of influence and influence is related to the component of annexation, integration and depopulation of villages (with influence power of 67.8).